(untitled) (مجلة المنصور, 2022)
Most of denoising methods have been proposed to perform on still images, while few have been proposed for video denoising and even less when it comes to color sequence. 3-D transform is a good tool for solving a video processing problem such as video denoising because it deals with spatial and temporal correlations between video frames. This paper aims to propose a methods for video denoising, named “Mixing Sub bands and Double Wiener filter Threshold methods” (MSDWTM). This method are performed with 2-D, 3-D FDWT and it gives a better result compared with the original methods using database of color AVI videos type. When the RMSE equal to (25.0963) it was decreased in 2D and 3-D FDWT method to (7.3511) and (7.1080) RMSE value.